A new lipase isolated from oleaginous seeds from Pachira aquatica (Bombacaceae) - Polizelli, Patricia Peres [UNESP]; Antonio Facchini, Fernanda Dell [UNESP]; Cabral, Hamilton [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Humana Press Inc, 2008)
A new lipase from seeds of Pachira aquatica was purified to homogeneity by SDS-PAGE obtaining an enzyme with a molecular weight of approximately 55 kDa. The purified lipase exhibited maximum activity at 40 degrees C and pH 8.0, for an incubation time of 90 min. Concerning temperature stability, at the range from 4 to 50 degrees C, it retained approximately 47% of its original activity for 3 h. The enzyme activity increased in the presence of Ca(++) and Mg(++), but was inhibited by Hg(++), Mn(++), Zn(++), Al(+++) and various oxidizing and reducing agents. The lipase was highly stable in the presence of organic solvents, and its activity was stimulated by methanol. The values of K(m) and V(max) were 1.65 mM and 37.3 mu mol mL(-1) min(-1), respectively, using p-nitrophenylacetate as substrate. The enzyme showed preference for esters of long-chain fatty acids, but demonstrated significant activity against a wide range of substrates.
Keywords: Enzyme; Lipase; seeds; Pachira aquatica; Hydrolysis